Extracellular vesicle-mediated communication between CD8+ cytotoxic T cells and tumor cells - Huang, Zeyu; Liu, Xuehui; Guo, Qinghao; Zhou, Yihang; Shi, Linlin; Cai, Qingjin; Tang, Shupei; Ouyang, Qin; Zheng, Ji (Frontiers in Immunology, 2024)
Tumors pose a significant global public health challenge, resulting in numerous fatalities annually. CD8+ T cells play a crucial role in combating tumors; however, their effectiveness is compromised by the tumor itself and the tumor microenvironment (TME), resulting in reduced efficacy of immunotherapy. In this dynamic interplay, extracellular vesicles (EVs) have emerged as pivotal mediators, facilitating direct and indirect communication between tumors and CD8+ T cells. In this article, we provide an overview of how tumor-derived EVs directly regulate CD8+ T cell function by carrying bioactive molecules they carry internally and on their surface. Simultaneously, these EVs modulate the TME, indirectly influencing the efficiency of CD8+ T cell responses. Furthermore, EVs derived from CD8+ T cells exhibit a dual role: they promote tumor immune evasion while also enhancing antitumor activity. Finally, we briefly discuss current prevailing approaches that utilize functionalized EVs based on tumor-targeted therapy and tumor immunotherapy. These approaches aim to present novel perspectives for EV-based tumor treatment strategies, demonstrating potential for advancements in the field.